Strengthening the role of community health workers through supportive supervision: A Scoping Review - Trimaya Cahya Mulat; Tirta Asprimi Anggraeni; Wahyudi Hardi; Muh Ihsan Kamaruddin; Jessy Andre Mangaya Takke (Journal Interdisciplinary Health, 2025)
Introduction: Community health workers (CHWs) are critical in expanding access to primary healthcare, particularly in underserved areas. Despite their essential role, CHWs often face challenges such as inadequate supervision, limited feedback, and lack of professional development. Supportive supervision, which emphasizes mentorship, joint problem-solving, and performance improvement, has emerged as a key strategy to strengthen CHW effectiveness and retention. Methods: This scoping review followed Arksey and O’Malley’s framework and the PRISMA-ScR guidelines. Relevant literature published between 2010 and 2025 was systematically searched in PubMed, Scopus, and Web of Science. Studies focusing on supportive supervision models, strategies, or outcomes for CHWs were included. Data were extracted and synthesized thematically to identify supervision approaches, implementation factors, and impacts on CHW performance. Results: Thirty-seven studies met the inclusion criteria. The findings revealed that supportive supervision enhances CHW motivation, service quality, and community trust. Effective supervision models were characterized by regular feedback, participatory monitoring, and peer learning. Barriers included insufficient resources, supervisor workload, and weak institutional support. Digital tools and community-based supervision showed promise in improving supervision frequency and data-driven decision-making. Conclusion: Supportive supervision plays a pivotal role in strengthening the performance and sustainability of CHW programs. Integrating structured, participatory, and technology-assisted supervision mechanisms into health systems can foster CHW empowerment, accountability, and long-term impact.